Epidemiologi Kecelakaan Lalu Lintas pada Pengemudi Sepeda Motor di Wilayah Kerja Kepolisian Sektor Loura Kabupaten Sumba Barat Daya - Heronimus Geli; Mustakim Sahdan; Dominirsep O. Dodo (Media Kesehatan Masyarakat, 2021)
Traffic accidents are still a health problem in low-income and developing countries. Traffic accidents cause injury, trauma and death as well as property loss. There are many factors associated with traffic accidents, both human factors, vehicles, and environmental factors. One of the dominant traffic accidents occurring is an accident for a motorcycle driver. This study aims to describe the epidemiological characteristics of traffic accidents in motorbike drivers. This research is a descriptive study using a cross sectional approach. The population in this study were all motorbike drivers who had an accident in the work area of ​​the Loura Sector Police, Southwest Sumba Regency. The number of samples in this study were 81 people. The results of this study indicate that the largest proportion of those who experience traffic accidents are male respondents in the 30-34 age category. From the aspect of vehicle conditions, the number of traffic accidents experienced by respondents was the condition of the vehicle brakes not functioning (brake failure), tires that were not flat / broken, and the condition of the vehicle lights that did not turn on. From the aspect of the physical condition of the road, the incidence of traffic accidents proportionally occurs both in the environmental conditions of the road with potholes and without holes. Meanwhile, in terms of lighting conditions, more accidents occur in places with low/dark lighting conditions.